The Impact of Vision Leadership on Organizational Effectiveness: The Mediating Role of Organizational Citizenship Behavior - Hani Nikookar; Parviz Ahi; Mohsen Akbari (مدیریت بهره وری, 2021)
What can facilitate achievement of organizational effectiveness in today's dynamic and turbulent world is an array of organizational leadership styles all of which might be subsumed under the umbrella term of vision leadership which can enhance organizational effectiveness by underscoring the very nature of the organization and its perspectives. In addition to efficient leadership, however, the employees’ meta-functional behaviors are crucial for attaining optimal organizational effectiveness.  The purpose of this applied and descriptive survey was, thus, to explore the extent to which vision leadership might impact organizational effectiveness with a focus on the mediating role of organizational citizenship behavior. The research sample comprised 192 employees at Guilan Agricultural Jihad Organization that was randomly recruited from a population of 385 based on Kukran formula. The research data were collected through a researcher-made and piloted questionnaire that was developed in the initial library research phase of the study to be employed in the subsequent field investigation to obtain the quantitative data necessary to answer the research questions. The collected data were analyzed via Pearson Correlation Coefficient and Structural Equation Modeling (SEM) using SPSS 25 and LISREL 8.8 software. The findings indicated that vision leadership could significantly promote organizational effectiveness and organizational citizenship behavior, and that organizational citizenship behavior had a significant positive impact on organizational effectiveness. That is to say, organizational citizenship behavior was found to mediate the effect of vision leadership on organizational effectiveness.